Optimization and Validation of HPLC Based Analytical Method for Simultaneous Determination of Thiamethoxm Residues - Akram, Sumia; Sultana, Bushra; Rafiq Aasi, Muhammad; Ali, Shaukat; Shahid, Muhammad (Asian Journal of Chemistry, 2015)
In present study, RP-HPLC-DAD protocol was optimized and calibrated over 0-50 μg/mL of standard thiamethoxam and subsequently applied to determine its residues in selected fruits (guava and citrus) and vegetables (cauliflower, tomato and okra) after 0, 1, 7, 14, 21 and 28 days of foliar spray (0.5 mg/plant). The results regarding method validation indicated that optimized HPLC-DAD method was linear over broad range of thiamethoxam concentration (0-60 μg/mL) with recovery rates 79.64-89.30 %. Furthermore, the incidence level of thiamethoxam in selected fruits (guava and citrus) and vegetables (tomato, cauliflower and okra) was found to be higher (0.3-0.89 μg/g) than maximum residue limit (MRL) established by Codex Alimentarius Commission (0.5 μg/g) after 0 and 1 day of foliar spray. While thiamethoxam residues observed after 7, 14 and 21 of foliar application were found to be within permissible limits. The persistence of thiamethoxam in selected fruits and vegetables decreased in the following order: okra, citrus, guava, cauliflower and least in tomato. Overall, it was speculated that optimized method might be quick, easy, cheap, effective, rugged and safe (QuEChERS) choice for thiamethoxam analysis of food commodities.